Vorstellungen von Studierenden und angehenden Lehrerinnen vom Mathematiklernen und -lehren (mathematica didactica, 2008)
In the English speaking scientific community there are numerous studies on preservice and prospective teachers’ beliefs of Mathematics teaching and learning. German publications refer mostly to teachers’ beliefs. The data collecting methods and the beliefs’ level of generality vary. In the following article beliefs are reconstructed from a concrete teaching-learning situation following Mayring’s Qualitative Content Analysis. The category system developed is a suitable instrument to analyse further classroom situations because it orientates on central classroom issues as task and student.